Germination responses of lycium humile, an extreme halophytic Solanaceae: Understanding its distribution in saline mudflats of the southern puna - Palchetti, Maria Virginia (2020)
Although knowledge about halophytic Solanaceae is scarce, it is known that several species within genus Lycium tolerate salinity. Lycium humile grows in highly saline soils in mudflats near saline Andean lakes. This study evaluated the germination responses of L. humile under different scarification methods, photoperiods, temperatures and saline conditions and, simultaneously, tested seedling survival under different iso-osmotic conditions. Dormancy and germination were found to be regulated by interactions with different factors, with the highest germination percentages being obtained by immersion in sulfuric acid, with a temperature of 25 °C and a temperature regime of 5/25 °C, under which seeds were neutrally photoblastic. As osmotic potential of saline solutions decreased, germination also decreased drastically but the seedling survival percentage was higher than 30 % at 600 mM NaCl. No seeds germinated in any of the polyethylene glycol (PEG) solutions and no seedling survival was observed from-1.2 MPa PEG solutions. More than 90 % of seeds incubated in NaCl were able to recover germination after being transferred to distilled water, independently of NaCl treatments. We concluded that the effects of extreme environmental conditions on germination responses and seed tolerance to salinity may determine the occurrence and restricted distribution of L. humile.